Analysis of complex chromosomal structural variants through optical genome mapping integrated with karyotyping - Zhu, Xiaoxi; Zheng, Huiling; Wan, Xue; Duan, Hang; Qi, Ying; Tang, Weijia; Yang, Fan; Yu, Limei (Frontiers in Genetics, 2025)
Background and ObjectiveParental chromosomal structural variations (SVs) represent a primary genetic factor contributing to recurrent spontaneous abortion (RSA). Individuals carrying SVs with complex chromosomal rearrangements (CCRs) typically exhibit a normal phenotype but are at an increased risk of miscarriage. Current standard clinical detection methods are insufficient for the identification and interpretation of all SV types, particularly complex and occult SVs, thereby presenting a significant challenge for clinical genetic counseling. Leveraging the high-resolution capabilities of optical genome mapping (OGM) technology, this study aims to rapidly and accurately identify complex SVs in RSA couples. Furthermore, it seeks to conduct an in-depth analysis of the genetic information within the breakpoint regions, thereby providing a more comprehensive scientific foundation for genetic counseling of RSA couples at both the cellular and genetic levels.Material and MethodsThis study involved the selection of nine subjects from two families who underwent genetic counseling at our hospital. Family 1 comprised a couple with the wife as a SVs carrier, and both her parents and brother were simultaneously analyzed for chromosomal karyotype. Family 2 included a couple with the husband as the SVs carrier, with his parents also undergoing chromosomal karyotype analysis. For SVs carriers whose karyotype analysis did not elucidate the recombination pattern, optical genome mapping (OGM) technology was utilized for further investigation, followed by Sanger sequencing to validate the OGM findings.ResultsIn Family 1, only the wife was identified as an SVs carrier. Initial chromosomal karyotype analysis suggested a karyotype of 46,XX,t (5; 6;8; 13; 15) (?). However, OGM analysis ultimately confirmed the karyotype as 46,XY,der (5)t (5; 13) (q35.2; q21.32), der (6)t (6; 8) (q25.3; q13.1)ins (6; 13) (q25.3; q21.32q21.33),der (8)t (6; 8) (q26; q13.1)ins (8; 13) (q13.1; q21.33q22.1),der (13)t (13; 15) (q21.32; q26.1)ins (13; 6) (q21.32; q25.3q26), der (15)t (5; 15) (q35.2; q26.1). Furthermore, OGM identified a novel translocation variant of the KIF7 gene that is associated with recurrent miscarriage. In Family 2, both the husband and his maternal parent were identified as SVs carriers. Nuclear type analysis revealed a karyotype of 46,XY,?t (1; 6) (q42; p21) (husband) and 46,XX,?t (1; 2) (p31.1; q24.1),?t (1; 6) (q42; p21) (mother). Through OGM detection and analysis, the final karyotype was determined to be 46,XY,ins (1; 6) (q42.2; p22.3p11.3) (husband) and 46,XX,der (1)t (1; 2) (p31.1; q24.1)ins (1; 6) (q42.2; p22.3p11.3), der (2) t (1; 2), der (6)ins (1; 6) (mother).ConclusionOGM technology facilitates the rapid and precise identification of complex chromosomal structural variations, effectively overcoming the limitations associated with traditional karyotype G-banding techniques in detecting intricate and cryptic SVs. This advancement substantially enhances the diagnostic rates of genetic etiology in patients experiencing RSA. The present study elucidates the specific manifestations of complex SVs using OGM technology, accurately pinpointing breakpoints and interpreting affected gene information. This provides novel reference approaches and evidence for disease assessment and genetic counseling in RSA patients. However, it is important to acknowledge certain limitations of this research: the study’s inclusion of only two RSA family cohorts (comprising nine participants) may limit the generalizability of its conclusions due to the small sample size, necessitating further validation through large-scale studies. Additionally, the causal relationship between KIF7 gene dysfunction and recurrent miscarriage remains to be experimentally verified in subsequent research.